2019
DOI: 10.3847/1538-4357/ab3a3c
|View full text |Cite
|
Sign up to set email alerts
|

Metal Abundances and Star Formation Rates of Emission-line Galaxies in and around the Boötes Void

Abstract: We explore the possible dependencies of galaxy metal abundance and star-formation rate (SFR) on local environment, focusing on the volume of space in and around the Boötes Void. Our sample of starforming galaxies comes from the second catalog of the Hα-selected KPNO International Spectroscopic Survey (KISS) which overlaps the void. This sample represents a statistically complete, line-fluxlimited ensemble of 820 star-forming galaxies, all of which possess metallicity and SFR estimates. We carry out two distinc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 94 publications
1
10
0
Order By: Relevance
“…In particular, we utilized the lower signal-to-noise ALFALFA galaxies with the idea that, at any given distance, they would have lower H I masses than their main ALFALFA catalog counterparts. In addition, they were selected to be located in the low-density region in front of the PPS (e.g., Haynes & Giovanelli 1986), because some studies have suggested that void galaxies tend to preferentially have lower metal abundances (e.g., Pustilnik et al 2016;Kniazev et al 2018; but also see Wegner et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we utilized the lower signal-to-noise ALFALFA galaxies with the idea that, at any given distance, they would have lower H I masses than their main ALFALFA catalog counterparts. In addition, they were selected to be located in the low-density region in front of the PPS (e.g., Haynes & Giovanelli 1986), because some studies have suggested that void galaxies tend to preferentially have lower metal abundances (e.g., Pustilnik et al 2016;Kniazev et al 2018; but also see Wegner et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While the vast majority of the voids have sizes near the middle of the mentioned range, there are examples of extremely large/small voids. As an example, the Bootes void is know as one of the largest objects in the Universe with an approximate radial size of 44-50 Mpc/h [43,44]. On the lower side of the size spectrum, mini-voids have been detected with sizes in the range of 0.7-3.5 Mpc/h [45,46].…”
Section: Cosmic Voidsmentioning
confidence: 99%
“…That is, for a given value of the [N II]λ6583/Hα ratio, the spread in [O III]λ5007/Hβ is larger than is typically seen in samples of ELGs. For example, comparison with Figure 1 in either Hirschauer et al (2018) or Wegner et al (2019), based on ELGs from the KISS objective-prism survey (Salzer et al 2000(Salzer et al , 2001Gronwall et al 2004), shows that many of the Hα Dots extend to much lower values of [O III]λ5007/Hβ. This is typically interpretted as an age effect, where lower excitation values indicate ionization from older stellar populations where the most massive O stars have already ended their lives.…”
Section: Spectroscopic Diagnosticsmentioning
confidence: 99%